Caracterização geofísica de área sob influência de necrópole no município de Caçapava do Sul – RS - (:unkn) unknown (Universidade Federal do Pampa, 2015)
A source of contamination / pollution are little known graveyard that when bad planned and leased, constitute a potential soil contamination risk and surface water and groundwater, besides the risk of human contact with such contaminants can cause. . The objective of this study was to perform resistivity profiles (CE) to demonstrate the presence of contamination plume, groundwater flow and zones possibly contaminated. With CE profiles carried out geophysical and geotechnical interpretation was performed by determining two main places where there is influence of the graveyard, and have determined the groundwater flow and where there is a source in the fracture zone, observed in field and evidenced by the 3D model generated apparent electrical resistivity. With the locations of determined anomalous conductivity zones were collected four samples of water points close to the cemetery and performed microbiological testing of total coliforms and E. coli. All samples were positive for total coliforms and only one has given negative for E. coli. Chemical analysis of metals was performed, however, was not obtained results due to the fact the method used (AAS atomized flame) does not detect amounts in µg / L. It was determined a high amount of aluminum when compared to the proposed WHO (2011). It was concluded that the contamination plume detected in the graveyard, has a spring located in fracture zone and is contaminated due to the influence of the graveyard, may have other microbiological agents and chemicals that were not possible to detect, making room for future work in the study area, adding knowledge of the phenomenon investigated. This field of study associated environmental impact of graveyards is little known and has significant importance because of the growing trend (increase in population density). The results were satisfactory in the detection and characterization in order to guide further research. The geophysical resistivity method was an effective and fast tool on initial recognition of a contaminated urban area.
Keywords: Eletrorresistividade; Contaminação; Águas subterrâneas; Electrical resistivity; Contamination; Groundwater